In vivo 'purging' of residual disease in CLL with Campath-1H. - Dyer, M; Kelsey, S; Mackay, H; Emmett, E; Thornton, P; Hale, G; Waldmann, H; Newland, A; Catovsky, D (1997)
We assessed the role of human CD52 antibody (Campath-1H) in six patients with chronic lymphocytic leukaemia (CLL) treated to maximal response with purine analogues (fludarabine/deoxycoformycin) in whom persistent leukaemic infiltration of blood and bone marrow had precluded autologous stem cell transplantation. Five patients achieved haematological and histological complete remission following Campath-1H and one had minimal focal residual CLL in a trephine biopsy. Autologous transplantation was performed in two patients without complications and with rapid haemopoietic engraftment. Treatment with Campath-1H may be of value in eradicating residual disease in CLL and may facilitate high-dose therapy in young patients.